2016
DOI: 10.1002/chem.201602805
|View full text |Cite
|
Sign up to set email alerts
|

Desymmetrizing Electron‐Deficient Diboranes(4): Diverse Products and Their Reactivity

Abstract: A comprehensive study of the reactivity of Lewis bases with dihalodiboranes(4) is presented. Diaryldihalodiboranes provide rearranged monoadducts when treated with cyclic (alkyl)(amino)carbenes, but halide-bridged adducts when treated with a range of pyridyl bases. Alternatively, the combination of diaminodihalodiboranes with strong carbene donors leads to boraborenium salts. The reduction and halide-abstraction reactivity of these adducts was also explored, leading to intramolecular C-H activation and the fir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
40
0
4

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(47 citation statements)
references
References 62 publications
3
40
0
4
Order By: Relevance
“…The B1−C1 bond to Ph L is nearly aligned with the plane of the sp 2 borane residue (torsion angle (C1,B1,B2,C22) 15.0(8) o ). The B−B bond length (1.772(9) Å) is typical for diborane(5) compounds and falls within the range observed for the analogous SIMes and Me cAAC adducts (1.762(4) and 1.772(5) Å, respectively) …”
Section: Resultssupporting
confidence: 70%
See 2 more Smart Citations
“…The B1−C1 bond to Ph L is nearly aligned with the plane of the sp 2 borane residue (torsion angle (C1,B1,B2,C22) 15.0(8) o ). The B−B bond length (1.772(9) Å) is typical for diborane(5) compounds and falls within the range observed for the analogous SIMes and Me cAAC adducts (1.762(4) and 1.772(5) Å, respectively) …”
Section: Resultssupporting
confidence: 70%
“…C−H activation at the isopropyl methine position of a Dipp substituent had also been observed by Robinson and co‐workers upon the reduction of [(IDipp)BCl(N( i Pr) 2 )]Cl with KC 8 in THF . Similarly, our group reported that the reduction of the diboranes(5) [Mes 2 BB(SIMes)Cl 2 ] and [Mes 2 BB( Me cAAC)Br 2 ] led to C−H activation at the ortho ‐methyl position of one mesityl ligand, in both cases leading to a bicyclic hydride‐bridged diborane …”
Section: Resultsmentioning
confidence: 84%
See 1 more Smart Citation
“…An example for a dication with three‐coordinate boron(II) atoms was presented by Siebert, Brothers and co‐workers, however, its structural characterization was merely based on theoretical methods . Very recently, Braunschweig and co‐workers structurally characterized a related three‐coordinate diboron(II) dication which was isolated in low yield after chloride abstraction from an unsymmetrical diborane(4) adduct precursor …”
Section: Figurementioning
confidence: 99%
“…Viele Arbeiten haben gezeigt, dass die Desymmetrisierung von Diboranen(4) [17a, 18] zu erhçhter Reaktivität, sowohl in der Aktivierung von kleinen Molekülen [19] als auch in Borylierungs-und Diborierungsreaktionen [20] sowie intramolekularen Umlagerungsprozessen [21] führt. Kürzlich berichteten wir über das Benzylphosphan-substituierte,u nsymmetrische Diboren 3 und sein gem-Isomer 4 (Schema 2), [22] das Borylborylen-Eigenschaftenaufweist.…”
Section: Angewandte Chemieunclassified